MODERN METHODS OF SMOOTH STARTING OF ASYNCHRONOUS MOTORS: THEIR TECHNOLOGIES AND INDUSTRIAL APPLICATIONS - Otabayev, Boburxon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article analyzes modern methods for the smooth starting of asynchronous motors. The problems that arise during the startup process of asynchronous motors and various effective methods to address them are discussed in detail, including soft starters, star-delta control, inverter-based control, and other technologies. The advantages, disadvantages, and industrial applications of each method are explained, along with the conditions and systems where they are most effective. Modern control systems and intelligent technologies are examined for their role in increasing motor efficiency, ensuring stable power supply, and optimizing production processes. The article provides important recommendations for optimizing asynchronous motors in various industrial sectors, contributing to energy efficiency, safety, and the long-term operation of equipment. This study serves as a valuable resource for implementing advanced technologies in asynchronous motor control.